1998
DOI: 10.1038/sj.bjp.0702022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic hypoxia on adrenoceptor responses of ovine foetal umbilical vessels

Abstract: 1 The eects of chronic hypoxia on a 1 -adrenoceptor-mediated contractions were investigated in foetal umbilical vessels obtained from near-term (*140 day gestation) pregnant sheep maintained near sea level (*300 m) and at high altitude (3820 m) from 30 day gestation. 2 Chronic hypoxia signi®cantly decreased contractile sensitivity of the umbilical vein to noradrenaline (pD 2 : 6.22+0.19 vs 5.67+0.09) and reduced the maximum response by 43%. Noradrenaline-induced contraction of the umbilical artery was abolishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“… 38 Finally, an elegant series of studies using long-term exposure of ovine pregnancies to the chronic hypobaric hypoxia of life at high altitude have reported impaired signaling in both β 1 - and α 1 -adrenergic receptor pathways in the heart and vasculature, respectively, in chronically hypoxic fetal sheep. 39 , 40 Combined, data from all these studies are consistent with the findings reported in the present investigation, indicating both alterations in the central autonomic regulation of cardiovascular function as well as changes in the reactivity of cardiovascular target organs to noradrenergic stimulation in the chronically hypoxic fetus. As several clinical studies have reported that the growth-restricted human infant displays compromised autonomic cardiovascular control as well as weak defenses to acute challenges, 8 , 10 data in the present study support that these adverse effects in the growth restricted fetus are likely to be due to those induced by chronic fetal hypoxia alone.…”
Section: Discussionsupporting
confidence: 91%
“… 38 Finally, an elegant series of studies using long-term exposure of ovine pregnancies to the chronic hypobaric hypoxia of life at high altitude have reported impaired signaling in both β 1 - and α 1 -adrenergic receptor pathways in the heart and vasculature, respectively, in chronically hypoxic fetal sheep. 39 , 40 Combined, data from all these studies are consistent with the findings reported in the present investigation, indicating both alterations in the central autonomic regulation of cardiovascular function as well as changes in the reactivity of cardiovascular target organs to noradrenergic stimulation in the chronically hypoxic fetus. As several clinical studies have reported that the growth-restricted human infant displays compromised autonomic cardiovascular control as well as weak defenses to acute challenges, 8 , 10 data in the present study support that these adverse effects in the growth restricted fetus are likely to be due to those induced by chronic fetal hypoxia alone.…”
Section: Discussionsupporting
confidence: 91%
“…One theory is that CH is associated with altered VSMC signaling in response to pressor agents. For example, decreased ␣ 1 -adrenergic receptor density and affinity may occur after CH and may be partly responsible for diminished vasoreactivity (10,46). In addition, CH is associated with attenuated coupling efficiency of ␣ 1adrenoreceptors to inositol (1,4,5)-trisphosphate (IP 3 ) and tissue contractile sensitivity to IP 3 (11,12,42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, investigations (8,26) in ovine uterine arteries demonstrate decreased ␣ 1 -adrenergic receptor number and affinity after hypoxia that may contribute to diminished vasoreactivity. In addition, it has been suggested that altered calcium sensitivity and/or handling in VSM may contribute to diminished vasoreactivity after long-term hypoxia (25). Although alterations in VSM function per se could contribute to altered vasoconstriction in this setting, additional evidence supports a role for a locally released vasodilator in this response.…”
Section: H35mentioning
confidence: 99%